ACROMEGALY: CURRENT PROBLEMS IN UKRAINE - Hradyk, Тетяна; Tsysnetska, Аліна (Actual Problems of Medicine and Pharmacy, 2022)
In Ukraine, primary diagnosis of orphan diseases is extremely low. In general, this is explained by the insufficient awareness of primary care doctors, the difficulties of diagnosing acromegaly (АМ). The majority of patients seek help at the stage of development of a bright clinical picture of AM. That is why family doctors and doctors of other specialties (therapists, dentists, endocrinologists, neurosurgeons, orthopedists, cardiologists) need to be highly informed in order to suspect and diagnose the disease in time.